Emotional branding : the new paradigm for connecting brands to people - Gobé, Marc, ....- (New York : Allworth Press, 2009)
A visionary approach to building powerful brand loyalty, this groundbreaking book shows marketers of any product or service how to engage today's increasingly cynical consumers on deeper emotional levels. 40 illustrations.
Includes bibliographical references and index.
Keywords: Branding (Marketing).; Consumers' preferences; Motivation research (Marketing).